Rancang Bangun Aplikasi Suicide Risk Idea Identification Menggunakan Rapid Application Develoment - Muhammad Amien Sidiq; Dr. Tenia Wahyuningrum; Ariq Cahya Wardhana (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2021)
Suicide is a deliberate act that results in death for oneself. Suicide is often associated with mental disorders such as depression, schizophrenia, bipolar disorder, and alcohol and drug abuse. Around 800 thousand people in the world are recorded to commit suicide each year, most of cases occur among teenagers. The lack of signs or symptoms in someone who wants to commit suicide is a big problem to reduce the number of deaths caused by suicide. Therefore, this research raised a theme related to these problems. research will design the Suicide Risk Idea Identification application using the Rapid Application Development method. RAD is a type of system development that is based on a series of iterative development cycles, using RAD method only takes 60-90 days. RAD has two types of methodologies, namely phase development and prototyping. The type of methodology used in this study is a prototyping methodology. Prototyping methodology applies all stages (analysis, design, and implementation) into action simultaneously. To facilitate early identification of suicidal ideation, a questionnaire is needed that discusses the severity of suicidal ideation and other attributes. SIDAS (suicidal identification attributes scale) is a questionnaire designed to identify suicidal thoughts and assess the severity of these thoughts.